SPINKS, Jennifer; EICHBERGER, Dagmar (eds.). Religion, the Supernatural and Visual Culture in Early Modern Europe: An Album Amicorum for Charles Zika. Leiden / Boston: Brill, 2016. ISBN 978-90-04-29726-5 (hardback) ISBN 978-90-04()-29901-6 (e-book). - Renders, Helmut (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2017)
O supernatural na cultura visual no início da Europa moderna: uma resenha de uma obra editada por Jennifer Spinks e Dagmar Eichberger em homenagem a Charles Zika Resenha de SPINKS, Jennifer; EICHBERGER, Dagmar (eds.). Religion, the Supernatural and Visual Culture in Early Modern Europe: <span style="font-size:11.0pt;font-family:";Bookman Old Style";,";serif";;mso-bidi-font-family:";Times New Roman";;color:windowtext;mso-ansi-language:EN-US;font-weight:normal;mso-bidi-font-weight:bold" lang="EN-US">An Album Amicorum for Charles Zika. Leiden / Boston: Brill, 2016 (Coletânea: Religion, the Supernatural and Visual Culture, vol.191). ISBN 978-90-04-29726-5 (hardback) ISBN 978-90-04()-29901-6 (e-book).